Atomic layer deposition of zinc oxide on microrough zirconia to enhance osteogenesis and antibiosis. Issue 18 (15th December 2019) - Yao, Litao; Wu, Xinghai; Wu, Shuyi; Pan, Xiaoyi; Tu, Junyi; Chen, Mengyu; Al-Bishari, Abdullrahman Mohammed; Al-Baadani, Mohammed A.; Yao, Lili; Shen, Xinkun; Liu, Jinsong
Abstract: Zirconia (ZrO2 ) is widely used as dental implants due to its aesthetics and biocompatibility. However, its bio-inert surface compromises the osseointegration. If bacterial infection occurs, the failure rate of traditional ZrO2 implant will further increase. Thus, to endow ZrO2 with antibacterial and osteogenic properties simultaneously, zinc oxide (ZnO) coated microrough structures were prepared on ZrO2 substrates (denoted as SA-ZrO2 /ZnO) by sandblasting/acid etching and subsequent atomic layer deposition (ALD) in our study. After 30 cycles of ALD, the target SA-ZrO2 /ZnO exhibited a similar appearance to unmodified ZrO2 . Uniform nano-granular ZnO were observed on both smooth and microrough ZrO2 substrates, but the latter loaded more Zn 2+ and released Zn 2+ for a longer time (over 14 d) due to its larger specific surface area. These ZnO nanoparticles exhibited superior bactericidal ability against Porphyromonas gingivalis, Staphylococcus aureus, and Escherichia coli, and provided more adhesion sites for MC3T3-E1 cells to significantly increase cell spreading and migration. Moreover, MC3T3-E1 cells on SA-ZrO2 /ZnO showed better proliferation and osteogenic differentiation abilities than other groups because of the synergistic effects of microrough structures and Zn 2+ . Thus, the SA-ZrO2 /ZnO may have a great potential for dental application.